Is there a Trade-off between Employment and Productivity? - Pramod N. (Raja) Junankar (Institute for the Study of Labor (IZA), 2013)
The aim of this paper is to analyse the possible trade-off between employment and productivity using panel data on world economies, developed and developing. We begin with the importance of productivity growth for developing countries, followed by a brief discussion of the concept of productivity and how it is measured. We discuss the concept of decent work and provide an index to measure decent work, and study its changes over time. First we provide some simple descriptive statistics and then carry out an econometric investigation using alternative estimation techniques. Our broad results suggest that there is a trade-off between employment and productivity.
Keywords: O11; O47; O17; 330; employment; productivity; trade-off; economic development